Enterprise Application Modernization: A Journey through Container-Based Cloud Architecture Transformation - Venkata Raghavendra Vutti (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the comprehensive journey of enterprise application modernization through container-based cloud architecture transformation, examining the critical aspects of this technological evolution. The article delves into the fundamentals of container-based architectures, analyzing their impact on organizational efficiency and operational capabilities. The article demonstrates the practical applications and benefits of containerization through detailed case studies from diverse sectors, including healthcare, retail, and enterprise-scale implementations. The article examines technical implementation considerations, focusing on orchestration strategies, deployment patterns, infrastructure requirements, and security considerations. It provides insights into best practices for application transformation, emphasizing assessment methodologies, testing approaches, and migration strategies. The article analysis extends to business impact evaluation, covering operational efficiency improvements, cost optimization benefits, and scalability achievements. The article culminates in exploring future considerations, examining emerging containerization and cloud-native evolution trends, and providing organizations with strategic insights for their digital transformation initiatives.